Implementation of social assistance policy for communities affected by the covid-19 pandemic in DKI Jakarta Province - Hartono Hartono; Dahyar Daraba; Ismail Nurdin; Mansyur Achmad (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The Covid-19 pandemic has significantly impacted health and the economy, leading many countries, including Indonesia, to launch social protection programs to mitigate the negative effects of the crisis. This research employs a qualitative research method with purposive sampling in selecting informants. Data analysis is conducted using the Miles and Huberman method, supported by the Nvivo 12 application. The research findings indicate that the implementation of social assistance policies for communities affected by the Covid-19 pandemic in DKI Jakarta Province involves two main aspects: policy content and policy implementation context. The policy content aspect encompasses factors such as influencing interests, types of benefits provided to the community, the expected extent of change, the roles of policymakers, the implementation of social assistance programs, and the limitations of available resources. On the other hand, the policy implementation context aspect includes power, interests, and strategies of the actors involved, the characteristics of institutions and authorities distributing social assistance, as well as the compliance levels and responses from policy implementers.